Mesoscopic Mapping of Ictal Neurovascular Coupling in Awake Behaving Mice Using Optical Spectroscopy and Genetically Encoded Calcium Indicators - Yang, Fan; Li, Jing; Song, Yan; Zhao, Mingrui; Niemeyer, James E.; Luo, Peijuan; Li, Dan; Lin, Weihong; Ma, Hongtao; Schwartz, Theodore H. (Frontiers in Neuroscience, 2021)
Unambiguously identifying an epileptic focus with high spatial resolution is a challenge, especially when no anatomic abnormality can be detected. Neurovascular coupling-based brain mapping techniques are often applied in the clinic despite a poor understanding of ictal neurovascular coupling mechanisms, derived primarily from recordings in anesthetized animals with limited spatial sampling of the ictal core. In this study, we used simultaneous wide-field mesoscopic imaging of GCamp6f and intrinsic optical signals to record the neuronal and hemodynamic changes during acute ictal events in awake, behaving mice. Similar signals in isoflurane-anesthetized mice were compared to highlight the unique characteristics of the awake condition. In awake animals, seizures were more focal at the onset but more likely to propagate to the contralateral hemisphere. The HbT signal, derived from an increase in CBV, was more intense in awake mice. As a result, the “ictal dip” in hemoglobin oxygenation became inconsistent and unreliable as a mapping signal. Our data indicate that CBV-based imaging techniques should be more accurate than BOLD-based imaging techniques for seizure mapping in awake behaving animals.